Finite element analyses for a study of hepatic cancer tissue destruction using monopolar and bipolar radio-frequency ablation - Tungjitkusolmun, S.; Boontaram, A.; Lertprasert, P.; Krairiksh, M. (My University, 2005)
This paper presents three-dimensional finite element analyses of radio-frequency hepatic tumor ablation. The analyses performed in this paper are composed of two systems. In the first system, the simulation was of monopolar ablation (one needle), while the second system was the simulation of bipolar ablation (two needles). We performed a preliminary study of thermal and electrical distributions of both systems. Additional simulations of bipolar ablation were performed to investigate the effect of spacing distance between two needle electrodes (2 cm, 3 cm, 4 cm, and 5 cm). The ablation duration used in all cases was 10 min, and the controlled maximum temperature was set to 90°C. From the results, the electric field in monopolar ablation appeared to be distributed uniformly between the electrode and the ground surface, but the electric field in bipolar ablation was focused in the regions between the two electrodes. For bipolar ablation, when the distances between the electrodes were 2 cm and 3 cm, the lesion created was contiguous and covered the areas surrounding both electrodes. However, when the distances between the electrodes were 4 cm and 5 cm, the lesions created were not contiguous and shaped similar to performing two monopolar ablation operations.
Keywords: Bipolar; Cancer tissue; Finite element; Hepatic; Radio-frequency; Three-dimensional